Comparative measurements of external radiation exposure using mobile phones, dental ceramic, household salt and conventional personal dosemeters. (January 2015) - Ekendahl, Daniela; Bulánek, Boris; Judas, Libor
Abstract: Because retrospective dosimetry utilises commonly occurring materials and objects, it is particularly useful in cases of large-scale radiation accidents or malevolent acts with radioactive materials where casualties are inflicted on the general public and first emergency responders. The aim of this study was to investigate whether retrospective dosemeters can provide dose estimates with comparable accuracy like conventional personal dosemeters. Using an external source of radiation 137 Cs and an anthropomorphic phantom, we simulated serious irradiation of a human body in anterior-posterior and rotational geometries. Retrospective luminescence dosimetry objects, such as mobile phones, dental ceramic and household salt, and conventional personal dosemeters (thermoluminescent and electronic) were fixed to the anthropomorphic phantom. The doses obtained were compared with specific reference values. In most cases, relative deviations between the measured doses and the reference values did not exceed 20%. As the retrospective and conventional dosemeters show no significant differences in laboratory conditions, the retrospective luminescence dosimetry objects represent a very promising tool if handled properly. Highlights: A serious external exposure of human body was simulated. Doses were measured using both retrospective and conventional dosemeters. Utilised retrospective dosimetry materials were alumina resistors from mobile phones, household salt and dental ceramic. Doses obtained were compared with reference values. Both retrospective and conventional dosemeters gave similar results.